The Development of Values and its Influence on Academic Performance - Filgueira Arias, Cándida; Hernández Suárez, María del Mar (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Training citizens capable of guiding their lives and at the same time being socially active seems to be one of the primary objectives that, from the different educational stages, they want to achieve. Learning some principles that guide the behavior of students is not an easy task and requires taking into account different aspects, both personal and social, however, achieving this goal is a fundamental achievement for the subject that will have an impact on their professional future. An educational proposal is made to work on values, understanding that it is a model that we consider favors the training of students in all its dimensions.